South Asians in “Asia’s World City”: Postcolonial Identity Struggles and Artistic Self-Representation in Hong Kong - Liu, Hong Yu (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2020)
With the government of Hong Kong having branded the city “Asia’s World City,” it has also proclaimed its commitment to fostering an inclusive society. However, critics question the effectiveness of the government’s policies in this regard, as many South Asians in Hong Kong continue to struggle with their identity due to social issues which have persisted since the beginning of the post-colonial period. Referencing observations shared by interviewees, this article discusses how South Asians engage in community art projects as a much-needed means of self-representation, given the perception of the state’s inadequate inclusion policies and its failure to achieve assimilatory multiculturalism within its institutions. Against this backdrop of perceived policy shortcomings is the emergence of a “dual” Hongkonger identity, which was observed through interviews with minority descendants, and which, it will be argued, is augmented through participation in community art projects. The findings and critical discussion presented in this article contribute significantly to our understanding of the problematic issues surrounding cultural inclusion, as well as the importance of self identity and community empowerment through artistic expression in Hong Kong specifically, and in East Asia more generally.